Influence of Social and Economic Status of Employed Ukrainian Citizens on Human Capital of Health - Zaiukov, I. V. (Visnyk of Vinnytsia Politechnical Institute, 2017)
The theoretical aspects of the influence of socio-economic status on the health of citizens have been analyzed. The main determinants that form the socio-economic status (by categories of the population, by types of economic activity, by the level of material incomes) and their influence on the health of the employed population of Ukraine are determined. It has been found out that with struggling of income inequality, promising directions for raising the level of human capital health, there is an intensification of the educational factor, professional growth and compliance with the principles of self-preservation.